1998
DOI: 10.1046/j.1523-1755.1998.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Unfavorable course of minimal change nephrotic syndrome in children with intrauterine growth retardation

Abstract: Our study demonstrated an unfavorable course of MCNS in children with IUGR. IUGR could therefore enable early identification of those children who are at risk of becoming frequent relapsers and of developing steroid dependency. This, however, should be confirmed in a larger number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
2
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 20 publications
2
39
2
1
Order By: Relevance
“…These cases, however, may be considered examples of the "two-hit " hypothesis, which proposes that the low nephron number (first hit) may influence the presentation and modify the course of a subsequent renal injury (second hit). Indeed, LBW has been associated with a worse outcome in diverse renal diseases, including idiopathic membranous nephropathy, minimal change disease, and IgA nephropathy (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…These cases, however, may be considered examples of the "two-hit " hypothesis, which proposes that the low nephron number (first hit) may influence the presentation and modify the course of a subsequent renal injury (second hit). Indeed, LBW has been associated with a worse outcome in diverse renal diseases, including idiopathic membranous nephropathy, minimal change disease, and IgA nephropathy (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that there is substantial variation in the nephron number in normal people without renal diseases (20,21). It is interesting that a low nephron number was shown to be associated with low birth weight, which was also shown to be associated with poor outcome of glomerular diseases, including IgAN (22)(23)(24). The second possibility is an effect of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adults with the lowest kidney volumes, examined in the context of current weight, had the highest rates of albuminuria and highest BP (23), tending to support a role of nephron underdosing in these pathologies. Lower birth weights have been associated with higher relapse rates in children with the nephrotic syndrome (86,87) and with progression in children with IgA nephropathy (88). Associations of birth weight with renal deaths are obscured by the competing effects of the higher numbers of cardiovascular and other nonrenal natural deaths that are predicted by renal markers (75)(76)(77)89) and by deficient documentation of the contribution of renal disease to natural deaths (90).…”
Section: Low Nephron Number Renal Disease and Renal Failurementioning
confidence: 99%
“…Evaluation through ESRD treatment registries poses problems of selection, especially in developing countries with restricted access; however, a study in the southeastern United States did show that ESRD patients tended to be of lower birth weights than matched controls (91). In some of these studies, the birth weight effect was more pronounced in women (20,83,84,86). Most, too, showed the important effect of higher levels of body fat in postnatal life in educing or exacerbating the adverse effects of lower birth weights, not only on renal disease but also on BP and metabolic profiles.…”
Section: Low Nephron Number Renal Disease and Renal Failurementioning
confidence: 99%